IMPLEMENTASI PROGRAM BACA TULIS AL-QUR’AN METODE TILAWATI DI MI MIFTAHUL ULUM KOTA BATU - Binti Nur Aini; Khoirul Asfiyak; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research explains about the implementation of the program how to read and write the Qur’an by tilawati method at Madrasah Ibtidaiyah Miftahul Ulum (MIMU) Batu City. It also answers some research questions as follows: (1) how to plan a program how to read and write the Qur’an by tilawati method at Madrasah Ibtidaiyah Miftahul Ulum (2) how to implement the program how to read and write the Qur’an by tilawati method (3) how to evaluate program how to read and write the Qur’an by tilawati method. Using a qualitative approach with descriptive type. This research has obtained research data from unstructured interview, passive participation observation and official documentation. The results of this research shows that: (1) MIMU has a good plan of program how to read and write Qur’an that is decide the purpose and method, prepare facilities, designate the person responsible and decide how to evaluate (2) almost all activites in the learning program how to read and write Qur’an at MIMU suitable with the standard provisions by the tilawati method (3) MIMU also has two ways to evaluate learning programs how to read and write the Qur’an well that is: daily evaluation and evaluation every sixs months.